Smart Zinc-Based Coatings with Chitosan–Alginate Nanocontainers Loaded with ZnO and Caffeine for Corrosion Protection of Mild Steel - Kamelia Kamburova; Nelly Boshkova; Tsetska Radeva; Nikolai Boshkov (Metals)
The development of environmentally friendly materials is a subject of increasing interest in corrosion protection research. The objective of the present investigation is to propose the preparation procedure of chitosan–alginate (CHI/ALG) nanocontainers loaded with zinc oxide (ZnO) nanoparticles or combining ZnO nanoparticles with corrosion inhibitor caffeine (CAF), both suitable for incorporation into the matrix of ordinary zinc coatings on mild steel substrates. The nanocontainers were synthesized through spontaneous polysaccharide complexation in the presence of ZnO nanoparticles and CAF using a cross-linking agent, namely tripolyphosphate (TPP). Dynamic light scattering and laser Doppler velocimetry measurements are used for evaluation of the size distribution and zeta potentials of the nanocontainers, both loaded or unloaded with CAF. Using UV-spectroscopy, entrapment efficiency and release amounts of CAF are quantitatively evaluated. The nanocontainers thus obtained were incorporated into the matrices of ordinary zinc coatings via co-electrodeposition with zinc from zinc sulfate solution, aiming to improve the corrosion protection of steel in corrosive environments containing chloride ions. The surface morphology and elemental composition of the electrodeposited hybrid coatings before and after treating in the model corrosive medium of 3.5% NaCl is studied by scanning electron microscopy (SEM). The cyclic voltammetry method (CVA) is applied to characterize the cathodic (electrodeposition) and anodic (dissolution) processes. The protective characteristics of the hybrid coatings are investigated by application of potentiodynamic polarization (PDP) curves and polarization resistance (Rp) measurements after a time interval of 40 days. The obtained results indicate that both hybrid coating types could prolong the life time of mild steel in aggressive Cl− ion-containing solution, combining the protection effect of sacrificial zinc with barrier (ZnO) and active (CAF) protective effects.